All We Need is Love? Trade-Adjustment, Inequality and the Role of the Partner - Katrin Stephanie Huber; Erwin Winkler (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
We examine the impact of Germany's trade integration with China and Eastern Europe from 1993 through 2008 on earnings inequality between households. We especially focus our attention on the role of assortative mating for the magnitude of this impact. Our analysis demonstrates that the trade shock worked towards an increase of earnings inequality, both in the short and in the medium run. Moreover, we illustrate that mating has become increasingly assortative in Germany, especially among low-skilled workers. The results of a counterfactual experiment reveal that this surge in the assortativeness of mating might deepen the negative impact of future trade shocks on earnings inequality between households and might consequently also reduce potential gains from trade.
Keywords: F16; J12; J31; 330